Hybrid business models in the sharing economy: The role of business model design for managing the environmental paradox - Reuter, Emmanuelle (My University, 2021)
With the primary emphasis on the tensions that platform organizations face between both for-profit and environmental value-creation goals, we know very little about the managerial drivers and mechanisms through which they realize multiple goals. Based on a qualitative, inductive case study of a UK-based digital platform's business model, we uncover the role of business model design. We find that the emphasis managers put on either the redistribution or the accessibility design theme shapes the environmental and financial value-creation, respectively and that a hybrid business model (i.e., realizing both for-profit and for-purpose value-creation) hinges on their integration. Two managerial drivers—strategic synergies and dynamic coupling—enable platform organizations to increase integration. We contribute to the literatures on hybrid business models, paradox, and business models for sustainability, suggesting that digital platforms not only create, but can actively manage the environmental paradox by integrating multiple design themes within hybrid business models.
Keywords: hybrid business model; business model design; sharing economy; digital platform; platform organization; platform management; digital economy; environmental paradox; hybrid organizing; accessibility; redistribution; sustainable technology; energy transition; decarbonization; flexibility